Toward sustainable agriculture in the tropics. (September 2019) - Erbaugh, James; Bierbaum, Rosina; Castilleja, Guillermo; da Fonseca, Gustavo A.B.; Hansen, Steffen Cole Brandstrup
Highlights: Identifies the processes by which sustainable agricultural production is being implemented and scaled-up in the tropics. Proposes a typology that, in broad terms, attempts to conceptualize the implementation of sustainable agriculture. Introduces a set of articles that advance research on sustainable agriculture production in the tropics. Abstract: Wide-scale transformation promoting sustainable agricultural production in the tropics will be crucial to global sustainability and development. Although contemporary agricultural production has increased alongside international demand, it has resulted in extensive changes in land cover, often at the expense of tropical forests and other native habitats. Conservation and development professionals from civil society, private foundations, multilateral and specialized international agencies, along with academic organizations and, increasingly, the private sector, have cited the urgent need to transform tropical agricultural production to meet current and future food needs without compromising environmental, economic, and sociocultural outcomes for present and future generations. This introduction identifies the processes by which sustainable agricultural production is being implemented and scaled-up in the tropics. We propose a typology that, in broad terms, conceptualizes the implementation of sustainable agriculture. This typology depicts how contributions to this special issue advance the understanding of sustainable agriculture in the tropics. Together, these articles demonstrate that implementing the sustainable production of agriculture often occurs through hybrid governance, with actors from the public sector, private sector, and civil society working together to define and implement interventions. Evaluation of sustainable agriculture production in the tropics often relies upon transdisciplinary teams that bring data, analysis, and firsthand knowledge together. Future research would do well to focus on sustainability outcomes as a combination of environmental and human well-being indicators; the composition and outcomes of different intervention mixes; and how implementation cycles influence subsequent definition, governance, and evaluation of sustainable agriculture in the tropics.